Implementasi Dana Corporate Social Responsibility (CSR) terhadap Kesejahteraan Masyarakat dan Kelestarian Lingkungan: (Studi Kasus PT. Bumi Daya Agrotamas Kota Subulussalam) - Syukri Syukri; Rabiatul Adawiyah; Muhaddis Muhaddis (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
PT. Bumi Daya Agrotamas aims to put pressure on the world of work to be better in carrying out all its production activities so that companies not only think about achieving maximum financial profits but also participate in preserving the environment around which the company is established... these impacts can be in the form of beneficial impacts and detrimental impacts. For companies, the various impacts are that companies oriented towards the economic aspect (profit) are also required to have a responsibility, both to the social aspect and to the environmental aspect. Based on the research background above, the author is interested in conducting research with the title